2021
DOI: 10.1039/d1nj02858h
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic synthesis of Pd-nanoparticles using Areca Nut Husk Extract: a greener approach to access α-keto imides and stilbenes

Abstract: An eco-friendly green method for one step synthesis of palladium nanoparticles and its synthetic utility has been reported. The phytochemicals like amines, alcohols, phenols present in the Areca Nut Husk...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 75 publications
0
13
0
Order By: Relevance
“…The intensity of the color increased in direct proportion to the incubation period, and the highest absorption peak indicated the maximal yield. Previous research has indicated that plants contain phenols and flavonoids with great antioxidant functions, enabling the synthesis of nanoparticles 53 , 54 . Evidence identifying various phytoconstituents in C .…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of the color increased in direct proportion to the incubation period, and the highest absorption peak indicated the maximal yield. Previous research has indicated that plants contain phenols and flavonoids with great antioxidant functions, enabling the synthesis of nanoparticles 53 , 54 . Evidence identifying various phytoconstituents in C .…”
Section: Discussionmentioning
confidence: 99%
“…The various analytical and spectroscopic techniques such as UV-VIS, FT-IR, FE-SEM, XRD, BET, TG-DTA and HR-TEM envisage the formation of Pd@CNTs catalyst (See the SI for more details). Based on our recent findings in this direction [8] and with the help of literature precedents [9] it is evident that the phytochemicals present in the aq. extract of Gliricidia sepium leaves reduces the Pd (II) to Pd (0) (See SI for GC-MS chromatogram).…”
Section: Introductionmentioning
confidence: 76%
“…The DTA graph indicates the maximum weight loss occurs at 216-415 C, which confirms the sustainability of δ-MnO 2 NPs even at a higher temperature (Figure 9b). [51][52][53][54] 3.9 | Temperature programmed desorption (TPD) analysis…”
Section: Thermogravimetric Analysis and Differential Thermal Analysis...mentioning
confidence: 99%